2017
DOI: 10.1089/cbr.2017.2181
|View full text |Cite
|
Sign up to set email alerts
|

In VitroIncorporation of Radioiodinated Eugenol on Adenocarcinoma Cell Lines (Caco2, MCF7, and PC3)

Abstract: Recently, the synthesis of radiolabeled plant origin compounds has been increased due to their high uptake on some cancer cell lines. Eugenol (EUG), a phenolic natural compound in the essential oils of different spices such as Syzygium aromaticum (clove), Pimenta racemosa (bay leaves), and Cinnamomum verum (cinnamon leaf), has been exploited for various medicinal applications. EUG has antiviral, antioxidant, and anti-inflammatory functions and several anticancer properties. The objective of this article is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…This peak was isolated from the whole extract, and purification of the peak was determinated by HPLC with the same isolation procedure. All HPLC chromatograms were uploaded as supplementary material . The isolated peak was sent to LC–MS analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This peak was isolated from the whole extract, and purification of the peak was determinated by HPLC with the same isolation procedure. All HPLC chromatograms were uploaded as supplementary material . The isolated peak was sent to LC–MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Dervis et al . synthesized AgNPs, and their characterization analysis showed that the size of AgNPs was between 25 and 50 nm and they have a cubic structure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pharmacological activities have been reported to eugenol: anti-inflammatory [ 28 ], antitumor [ 29 ], antibacterial [ 30 ], antifungal [ 31 , 32 ], antipyretic [ 33 ], anesthetic [ 34 ], and analgesic activities [ 35 ]. Considering the importance of eugenol as bioactive molecule and its presence in various foods and medicinal plants, this review discusses its role in the inflammatory response in experimental models, including animals and cell culture tests, demonstrating its antioxidant profile and potential therapeutical application against inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…21 Eugenol has extensive pharmacological effects, such as inhibiting the NF-kB pathways, participating in immune regulation and the anti-inammatory response, blocking the activity of xanthine oxidase, affecting temperaturesensitive neuron discharge and antipyretic activities. [22][23][24][25][26] Moreover, eugenol is used for animal anaesthesia, mosquito repellent and the promotion of drug permeation absorption. Eugenol shows potential for application in the prevention and treatment of certain tumours.…”
Section: Introductionsmentioning
confidence: 99%